2018
DOI: 10.1103/physreva.97.032501
|View full text |Cite
|
Sign up to set email alerts
|

Reducing detrimental electrostatic effects in Casimir-force measurements and Casimir-force-based microdevices

Abstract: It is well known that residual electrostatic forces create significant difficulties to precise measurements of the Casimir force and to wide use of Casimir-operated microdevices. We experimentally demonstrate that with the help of Ar-ion cleaning of the surfaces it is possible to make electrostatic effects negligibly small as compared to the Casimir interaction. Our experimental setup consists of the dynamic atomic force microscope supplemented with an Ar-ion gun and argon reservoir. The residual potential dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 50 publications
5
81
0
Order By: Relevance
“…1 is a rectangular cantilever. As compared to previous experiments [12][13][14][15]17], the precision of force measurements here was improved by increasing the sensitivity of the cantilever through a decrease of its spring constant. The cantilever spring constant is given by [62]…”
Section: Upgraded Setup With a Two-step Surface Cleaningmentioning
confidence: 73%
See 3 more Smart Citations
“…1 is a rectangular cantilever. As compared to previous experiments [12][13][14][15]17], the precision of force measurements here was improved by increasing the sensitivity of the cantilever through a decrease of its spring constant. The cantilever spring constant is given by [62]…”
Section: Upgraded Setup With a Two-step Surface Cleaningmentioning
confidence: 73%
“…The experimental setup was placed inside a stainless steel vacuum chamber consisting of a mechanical scroll pump and a turbo pump connected in series to achieve a pressure down to 10 −9 Torr ≈ 1.3 × 10 −7 Pa, and an ion pump for further reduction (see Refs. [12,17] for details). During the force measurements only the ion pump was used in order to reduce the background mechanical noise to a minimum.…”
Section: Upgraded Setup With a Two-step Surface Cleaningmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, in a number of experiments performed by two different groups [11][12][13][14][15][16][17][18][19][20][21] it was found that the measurement results exclude theoretical predictions of the Lifshitz theory obtained using an extrapolation of the optical data by means of the Drude model. The same results turned out to be in agreement with theory if the optical data reflecting the role of core (bound) electrons are extrapolated down to zero frequency by the free-electron plasma model [11][12][13][14][15][16][17][18][19][20][21]. An important role in these comparisons is played by the contribution of the zero-frequency term of the Lifshitz formula which depends heavily on the extrapolation used.…”
Section: Introductionmentioning
confidence: 93%